The Impact of Memrise Application on Iranian EFL Learners’ Collocation Learning and Retention - Esmaeili, Zeynab; Shahrokhi, Mohsen (Universitas Negeri Makassar, 2020)
This study aimed at investigating the effect of Memrise application on Iranian EFL learners’ collocation learning and retention. To this end, a quasi-experimental design was used. 75 Iranian intermediate EFL learners studying English at a private language institute, namely Farahan, Iran were selected to participate in the study based on convenience sampling in the form of two intact classes. The scores obtained were entered into SPSS software for the purpose of data analysis. The results of data analysis showed that Memrise application had a statistically differential effect on collocation learning of Iranian EFL learners. Moreover, it was demonstrated that Memrise application had a statistically differential effect on collocation retention of Iranian EFL learners. In addition, it was proved that there was a significant difference between the immediate post-test scores Iranian EFL learners who received Memrise application and those who received traditional teaching. Finally, it was indicated that there was a statistically significant difference between the delayed post-test scores of Iranian EFL learners who received Memrise application and those who received traditional teaching. Key Words: Collocation Learning; Collocation Retention; Memrise application; Mobile Assisted Language Learning (MALL); Computer Assisted Language Learning (CALL).